2017
DOI: 10.1002/dvdy.24581
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish sin3b mutants are viable but have size, skeletal, and locomotor defects

Abstract: Surprisingly, Sin3b is not essential in zebrafish. sin3b mutants show a decrease in fitness, small size, changes to locomotor behavior, and delayed bone development. We did not detect a role for Sin3b in cell proliferation. Our analysis of the sin3b mutant revealed a more nuanced requirement for zebrafish Sin3b than would be predicted from analysis of mutants in other species. Developmental Dynamics 246:946-955, 2017. © 2017 Wiley Periodicals, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Zebrafish mutants harboring truncating mutations in sin3b display locomotion defects, delayed ossification, and shortened body length. 26 With the exception of variable growth phenotypes in our cohort (Table 1), these aberrant zebrafish mutant phenotypes did not have discrete anatomical correlates with features of our human cohort. To test whether we could link anatomical phenotypes observed in individuals with SIN3B haploinsufficiency, we disrupted the SIN3B ortholog in zebrafish (Ensembl: ENSDARG00000062472, GRCz10; 63% identity, 74% similarity versus human [GenBank: NP_056075.1]; Figure S2A).…”
mentioning
confidence: 56%
“…Zebrafish mutants harboring truncating mutations in sin3b display locomotion defects, delayed ossification, and shortened body length. 26 With the exception of variable growth phenotypes in our cohort (Table 1), these aberrant zebrafish mutant phenotypes did not have discrete anatomical correlates with features of our human cohort. To test whether we could link anatomical phenotypes observed in individuals with SIN3B haploinsufficiency, we disrupted the SIN3B ortholog in zebrafish (Ensembl: ENSDARG00000062472, GRCz10; 63% identity, 74% similarity versus human [GenBank: NP_056075.1]; Figure S2A).…”
mentioning
confidence: 56%
“…The SIN3B gene encodes a transcription corepressor which has an important role in histone deacetylation and transcriptional repression ( Latypova et al, 2021 ). An animal model showed that Sin3b knockout mice and zebrafish sin3b mutants express skeletal and growth defects ( David et al, 2008 ; Moravec et al, 2017 ). Sin3b knockout mice also showed defects in blood differentiation, whereas zebrafish sin3b mutants showed locomotor defects ( Cantor and David, 2017 ; Moravec et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…An animal model showed that Sin3b knockout mice and zebrafish sin3b mutants express skeletal and growth defects ( David et al, 2008 ; Moravec et al, 2017 ). Sin3b knockout mice also showed defects in blood differentiation, whereas zebrafish sin3b mutants showed locomotor defects ( Cantor and David, 2017 ; Moravec et al, 2017 ). Although STRING analysis did not show any correlation with a specific phenotype (data available online), both g:Profiler analysis and the literature have reported that haploinsufficiency of SIN3B causes an ID and ASD phenotypes ( Latypova et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the vertebrate lineage, a duplication event gave rise to two Sin3 genes, Sin3a and Sin3b . In zebrafish, however, there are three Sin3 genes, sin3aa , sin3ab, and sin3b, as a result of a second gene duplication event specific to teleost fish [ 36 ]. The paralogs Sin3aa and Sin3ab are 78% identical to each other and 50% identical to their ortholog Sin3b, exhibiting high levels of similarity between the PAH and HID domains.…”
Section: Sin3 Isoform Conservation Across Speciesmentioning
confidence: 99%